Simulation, Modeling, and Programming for Autonomous Robots - Carpin, S. (Springer, 2017)
This book constitutes the refereed proceedings of the First International Conference on Simulation, Modeling, and Programming for Autonomous Robots, SIMPAR 2008, held in Venice, Italy, in November 2008.